STUDY OF ADSORPTION POTENTIAL OF YEAST SLUDGE AGAINST AFLATOXINS IN BROILER CHICKS - I. Hashmi; T. N. Pasha; M. A. Jabbar; M. Akram; A. S. Hashmi (Journal of Animal and Plant Sciences, 2006)
A study was conducted to investigate the adsorption potential of yeast sludge against aflatoxins produced in broiler feed. Productive, clinical and immune aspects of broilers feed on aflatoxins with yeast sludge in diet were also studied. Two hundred and forty broiler chicks of (one week age) were fed experimental diets for five weeks. In the present study the sludge has been used @ 1% of feed to reduce the toxic effects of aflatoxins through its adsorption potential. Three levels of aflatoxins (100, 200 and 300 ppb) along with two levels of yeast sludge (0 and 1%) were supplemented in commercial diet. The results showed that the feed intake, weight gain, feed conversion ratio were non-significantly (P>0.05) different among birds provided yeast sludge supplemented diet and birds which were not supplemented with yeast sludge. However it was observed that supplementation of yeast sludge increased the level of serum total protein, serum albumin and antibody titer of ND, and reduced the activity of alanine transaminase in serum, aflatoxins concentration in liver and mortality. It was found that 1% yeast sludge worked effectively at 100 and 200 ppb aflatoxins level, but at 300 ppb aflatoxins level the concentration of yeast sludge was not adequate to detoxify the highest level of aflatoxins effectively. However an apparent improvement has been observed. It was also found that if 100 ml yeast sludge contains 8.96 gm yeast cells, it contains 0.26% mannan oligosaccharide, which is the principal compound that bind the aflatoxins.
Keywords: Aflatoxin; yeast sludge; adsorption